Hubungan antara Social Support dan Mental Toughness pada Atlet Futsal Remaja di Kota Padang - Ramadhan, Aditya (Lembaga Yasin AlSys, 2025)
This study is motivated by the low level of mental toughness among youth futsal athletes in Padang City when facing competitive pressure, which can negatively affect their performance on the field. One factor suspected to influence this condition is social support. The aim of this research is to examine and analyze the relationship between social support and mental toughness among youth futsal athletes. A quantitative correlational approach was used, involving 150 male futsal athletes aged 17–22 years, selected through purposive sampling. The research instruments included a mental toughness scale by Gucciardi and a social support scale by Sarafino. Data analysis was conducted using Pearson’s product moment correlation after confirming normality and linearity of the data. The results revealed a positive and significant relationship between social support and mental toughness, with a significance value of p = 0.032 (< 0.05) and a correlation coefficient of r = 0.175. These findings suggest that higher levels of social support are associated with higher levels of mental toughness, although the correlation is relatively low. Most respondents in this study fell within the moderate category in terms of both social support and mental toughness. The conclusion of this study is that social support plays an important role in shaping and strengthening the mental toughness of youth futsal athletes, and should therefore be considered in athlete development programs. The implications of this study highlight the need for involvement from families, coaches, and peers in creating a supportive social environment to enhance the psychological resilience of athletes under competitive pressure.